And then you were gone : a novel - Jacobs, R. J. (Crooked Lane, 2019)
After years of learning how to manage her bipolar disorder, Emily Firestone finally has it under control. Even better, her life is coming together: shes got a great job, her own place, and a boyfriend, Paolo, who adores her.